Digital Marketing for SMEs Cidokom Village Plant Cultivation Group - Puspita Dewi, Maya; Larasati Hazrati Havidz, Ikramina; Ria Atmaja, Dodi; Yulian Firmansyah, Bonifasius (Majalah Ilmiah Bijak, 2022)
The application of a digital strategy needs to be considered for owners, in this case, SMEs. Especially during a pandemic l, which makes various kinds of business activities have a hard time. This study aims to find out how high the use of digital strategies in SMEs is and how to implement them. This study identifies a digital strategy implementation model consisting of five phases that are "Passive acceptance," "Connection," "Immersion," "Fusion," dan "Transformation.".